2020
DOI: 10.1002/jhbp.828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Billroth‐II versus Roux‐en‐Y reconstruction for gastrojejunostomy after pancreaticoduodenectomy on delayed gastric emptying: A meta‐analysis of randomized controlled trials

Abstract: Background/Purpose: Delayed gastric emptying (DGE) is one of the most common complications after pancreaticoduodenectomy (PD). The aim of the present metaanalysis was to evaluate the effect of Billroth-II(B-II) versus Roux-en-Y (R-Y) reconstruction for gastrojejunostomy on DGE after PD. Methods: A systematic literature search was performed using the electronic database MEDLINE (via PubMed and OVID), EMBASE and Cochrane Central Register of Controlled Trials (CENTRAL) of the Cochrane Library to select pertinent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…Hormonal dysbalances after the resection of the duodenum, gastric ischemia and denervation due to the mobilization and lymphadenectomy are proposed causes for the occurrence of DGE after PD [ 18 ]. Furthermore, associations with reconstructional aspects (Billroth II vs. Roux en Y, antecolic vs. retrocolic) have been discussed [ 9 , 19 , 20 ]. These classical risk factors do not apply for DP procedures as the duodenum remains in situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal dysbalances after the resection of the duodenum, gastric ischemia and denervation due to the mobilization and lymphadenectomy are proposed causes for the occurrence of DGE after PD [ 18 ]. Furthermore, associations with reconstructional aspects (Billroth II vs. Roux en Y, antecolic vs. retrocolic) have been discussed [ 9 , 19 , 20 ]. These classical risk factors do not apply for DP procedures as the duodenum remains in situ.…”
Section: Discussionmentioning
confidence: 99%
“…A previous StuDoQ|Pancreas-based analysis of DGE following pancreaticoduodenectomy (PD) identified higher age, longer duration of surgery, reconstruction as pancreaticogastrostomy (PG), postoperative pancreatic fistula (POPF), insufficiency of the hepaticojejunostomy and other surgical complications as risk factors for the occurrence of DGE [ 2 ]. Additionally surgical techniques, sepsis or intraabdominal abscesses are discussed as risk factors for DGE in the literature [ 7 , 9 , 10 ]. As there is no known causal therapy, the prevention of DGE should be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…[54,55] The main purpose of Roux-en-Y reconstruction was to prevent retrograde biliary infection caused by bile reflux, premature activation of pancreatic enzymes, and bile reflux gastritis. However, based on the results of 4 RCTs and 10 observational studies, [50,52,56,57] no statistically significant differences were found between the two groups in any outcome indicators except operation time, which was longer for the patients undergoing Roux-en-Y reconstruction. These data could well explain the greater use of Billroth-II than Roux-en-Y in GJ reconstruction (74% vs 26%).…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то что в значительной части публикаций исследовали реконструкцию Б2 и гастроеюноанастомоз по Ру после ПДР, патогенетического обоснования роли этих вариантов реконструкции в развитии гастростаза не обнаружили. В метаанализе, включившем 5 РКИ [32], был сделан вывод, что при идентичной частоте гастростаза в целом после реконструкции Б2 частота клинически значимого гастростаза была меньше. Однако стоит отметить, что этот метаанализ имеет ряд ограничений.…”
Section: возможности профилактики гастростазаunclassified